2022
DOI: 10.1111/gcb.16501
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of photosynthetic traits across soil and climate gradients

Abstract: Least-cost theory" posits that C 3 plants should balance rates of photosynthetic water loss and carboxylation in relation to the relative acquisition and maintenance costs of resources required for these activities. Here we investigated the dependency of photosynthetic traits on climate and soil properties using a new Australia-wide trait dataset spanning 528 species from 67 sites. We tested the hypotheses that plants on relatively cold or dry sites, or on relatively more fertile sites, would typically operate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 109 publications
(170 reference statements)
1
3
0
Order By: Relevance
“…Our results revealed that soil water was positively associated with community-level SLA for both community types (Figure 3B), while no other significant associations with soil water or light availability were observed (Figures 3A, C). These significant results align with the literature as SLA is associated with higher growth and photosynthesis rates, which heavily rely on water and nutrient supply (Xu and Zhou, 2011;Flexas et al, 2012;McAdam and Brodribb, 2015;Novick et al, 2016;Lambers and Oliveira, 2019;Westerband et al, 2023). Surprisingly, soil water was not associated with leaf N, while this trait is correlated with SLA (Figure 5B) and their shared position on the "fast" end of the LES (Wright et al, 2004;Diaz et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Our results revealed that soil water was positively associated with community-level SLA for both community types (Figure 3B), while no other significant associations with soil water or light availability were observed (Figures 3A, C). These significant results align with the literature as SLA is associated with higher growth and photosynthesis rates, which heavily rely on water and nutrient supply (Xu and Zhou, 2011;Flexas et al, 2012;McAdam and Brodribb, 2015;Novick et al, 2016;Lambers and Oliveira, 2019;Westerband et al, 2023). Surprisingly, soil water was not associated with leaf N, while this trait is correlated with SLA (Figure 5B) and their shared position on the "fast" end of the LES (Wright et al, 2004;Diaz et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…However, V cmax showed a significant relation with leaf nitrogen concentration per unit area (N a , Figure 4c). These results suggest a down-regulation of V cmax in spring in cork oak according to the least-cost theory [42,43], which posits that the costs of carboxylation and water loss during photosynthesis are balanced with the costs of acquisition and maintenance of resources (e.g., nitrogen) needed for photosynthesis. By allocating less nitrogen to the photosynthetic metabolism, or Rubisco in particular, while maintaining high A max , more nitrogen can be allocated to other sinks, such as the growth of new leaves or other tree components.…”
Section: Discussionmentioning
confidence: 86%
“…This largely confirmed our third hypothesis. However, these physiological processes and the underlying mechanisms on the relationships between photosynthesis and resource use for the different PFTs such as xylophyta and herb groups need further to be explored (e.g., [ 78 , 79 , 82 ] ).…”
Section: Discussionmentioning
confidence: 99%